102 A 17 Year Review Of Discharges On Medical Grounds Due To Cardiovascular Disease In The United Kingdom Armed Forces. (31st May 2014) - Cox, Andrew; Backholer, Ben; Byrne, Edd; Pratt, Gavin; Harrison, Kate; Wilson, Duncan; Sharma, Sanjay
Abstract : Background: Epidemiology studies of cardiovascular disease in young athletic populations usually concentrate on mortality due to methodological convenience, but cardiovascular disability is also likely to be prevalent.Medical discharges from the UK Armed Forces may provide an insight to the underlying burden of cardiovascular disease. Methods: All discharges on medical grounds were reported to Defence Statistics and categorised using the WHO ICD-10 system.Discharges due to cardiovascular disease between April 1995 to March 2012 were compiled with crude rates recorded per 100, 000 Service years. Results: 651 cardiovascular discharges were recorded over 2, 935, 430 Service years (rate 22.18 per 100, 000). Males comprised 91.3% of the population but only 88.8% of discharges. Cardiac causes accounted for 37.2% of cases (242 discharges, rate 13.93 per 100, 000), with ischaemic heart disease the most frequent diagnosis (92 discharges, rate 3.13 per 100, 000). Other important cardiac diagnoses were cardiomyopathy, arrhythmia, conduction and congenital abnormalities, valve dysfunction and infectious diseases. Extra-cardiac disease accounted for 63% of diagnoses (409 discharges, rate 13.93 per 100, 000) with Reynaud's syndrome (85 discharges, rate 2.90 per 100, 000) stroke (83 discharges, rate 2.83 per 100, 000) and venous diseases, including thromboembolism (61 discharges, rate 2.08 per 100, 000) the most frequent. Discussion: Cardiovascular disease causes a significant and unrecognised morbidity burden on the UK military. Much is due to stroke and ischaemic heart disease and policies directed at reducing disease development may be preventative. Effective screening for inherited or congenital disorders at the point of recruit entry would allow early identification and intervention in these disorders.